UNIVERSITY PHYSICAL EDUCATION AND SPORTS ADVANCEMENT PROGRAM: PROVISIONS AND ANALYSIS - Merzlyakova, G.V.; Novokreshchenov, V.V.; Alabuzhev, A.E. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop an Udmurt State University Physical Education and Sports Progress Program for the period up to 2030 (hereinafter referred to as the Program). Methods and structure of the study. We used the following methods in the study: analysis of the valid legal and regulatory documents for the physical education and sports sector management and the relevant physical education and sports service policy documents for universities; questionnaire surveys using the Google Forms online service, interviews, and mathematical tools for the questionnaire survey data processing and analyses. The survey data produced by the Google Forms were instantly processed and analyzed. We sampled the 1-3-year students attending the university physical education and sports classes for questionnaire survey-1 in March 2018 (n=689) and questionnaire survey-2 in October 2020 (n=345). Results and conclusion. The recent federal governmental policy documents to encourage the national physical education and sports progress require from the national higher educational establishment taking challenging projects to increase their habitually sporting student populations. The federal strategy sets the goals that should be attained on a systematic basis, with every university expected to develop and implement its own physical education and sports progress program. These university physical education and sports progress programs for the period up to 2030 should respect the following: every university’s university sports progress history and traditions for the whole service period; key university sports progress provisions; university physical education and sport service assets/ infrastructure and accessibility; interests and needs of the student community profiled by the questionnaire survey; best practices and experiences of the peer universities implementing the similar Programs.